Christopher Seitz and the Priority of the Christ Event - Boersma, Hans (Pro ecclesia, 2020)
While Seitz’s The Elder Testament: Canon, Theology, Trinity shows some sympathy for historical-critical readings of the Old Testament, he rightly insists on a theological starting point: he maintains that the Old Testament itself provides providentially inserted clues that demand a Trinitarian reading, and so he maintains that the Old Testament itself “pressures forth” a Christian reading of the text. We should keep in mind, however, that it is only through the acknowledgement of the ontological priority of the Christ event (and of the church’s identity within the Christ event) that the Spirit enables us to recognize the hidden, deeper meanings of the text.